1999
DOI: 10.1046/j.1365-2141.1999.01727.x
|View full text |Cite
|
Sign up to set email alerts
|

X‐chromosome inactivation analysis of isolated Reed‐Sternberg cells in nodular sclerosing Hodgkin's disease

Abstract: Summary. In spite of several studies of immunoglobulin (Ig) gene rearrangements in whole Hodgkin's disease (HD) tissues and in isolated single Reed-Sternberg (RS) cells, the issue of clonality of the RS cell in HD remains incompletely resolved. Analysis of X-chromosome inactivation patterns (XCIPs) can be used to determine whether cell populations are clonal in origin. By PCR ampli®cation of the human androgen receptor (HUMARA) loci using nested primers, we have studied XCIPs in six cases of HD of the nodular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…23 In cHL, however, X-chromosome inactivation analysis has been performed just to evidence clonality of HRSC. 56 Of note, the androgen receptor can be activated through androgen independent pathways 57 such as the PIK3CA pathway. We identified a loss of genetic material in the PIK3CA gene in a patient with an amplification in the AR gene.…”
Section: Discussionmentioning
confidence: 99%
“…23 In cHL, however, X-chromosome inactivation analysis has been performed just to evidence clonality of HRSC. 56 Of note, the androgen receptor can be activated through androgen independent pathways 57 such as the PIK3CA pathway. We identified a loss of genetic material in the PIK3CA gene in a patient with an amplification in the AR gene.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that TKS-1, an EBV-positive LCL cell line that was spontaneously established from a patient with RA, expresses the HL markers CD15 and CD30 [26], and that PMA altered their expression to levels similar to those of H-RS cells. Hsu and Hsu examined the effect of PMA on the surface phenotype of H-RS cells obtained from the spleens of patients with HL and showed that CD15 expression persisted for at least three days, whereas that of CD30 gradually declined [24].…”
Section: Discussionmentioning
confidence: 99%